The Relationship between BPJS Patient Satisfaction Level and Service Quality in Hospitals - Dahlan, Muslih; Widjanarko, Bagoes; Jati, Sutopo Patria (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
Hospital is a health service institution that provides comprehensive personal health services, including medical services, medical rehabilitation and maintenance services. These services are carried out through the emergency department, outpatient unit and inpatient unit. Specialists and subspecialist doctors in hospitals provide outpatient services. By reviewing published works in 10 journals from 2015 to 2022, we examine the relationship between BPJS patient satisfaction level and service quality with the keywords service satisfaction journal search, BPJS, and Hospitals. The analytical tool used was PICO. The results of the study found that based on satisfaction indicators, there were seven dissatisfied journals (66.7%) on all the hands described (Tangibility, Reliability, Responsiveness, Assurance and Empathy) from 9 journals (90%) dissatisfied with BPJS services in hospitals. Patient satisfaction will impact the quality of service in a hospital.